Art in Europe 1700-1830 - Craske, Matthew (Oxford history of art, 1997)
Taking a critical view of such conventional categorizations as the 'Rococo', the 'Neo-Classical', and the 'Romantic', Matthew Craske creates a totally new and vivid picture of eighteenth- and early nineteenth-century art in Europe. He engages with crucial thematic issues such as changes in 'taste' and 'manners' and the impact of enlightenment notions of progress. At the same time he goes well beyond the usual geographical limits of surveys to take in St Petersburg, Copenhagen, Warsaw, and Madrid.